Efficacy, tolerability, and safety of eptinezumab in patients with a dual diagnosis of chronic migraine and medication‐overuse headache: Subgroup analysis of PROMISE‐2. Issue 1 (13th December 2020) - Diener, Hans‐Christoph; Marmura, Michael J.; Tepper, Stewart J.; Cowan, Robert; Starling, Amaal J.; Diamond, Merle L.; Hirman, Joe; Mehta, Lahar; Brevig, Thomas; Sperling, Bjørn; Cady, Roger
Abstract: Objective: To evaluate the efficacy, tolerability, and safety of eptinezumab 100 and 300 mg compared with placebo in patients with the dual diagnosis of chronic migraine (CM) and medication‐overuse headache (MOH). Background: Eptinezumab, a humanized monoclonal antibody targeting calcitonin gene‐related peptide, may be effective for treating patients with a dual diagnosis of CM and MOH. Methods: PROMISE‐2 (NCT02974153) was a double‐blind, randomized, placebo‐controlled, phase 3 study that comprised a screening visit, a 28‐day pretreatment period, and a 32‐week study duration. Patients in this exploratory analysis of a prespecified subgroup had confirmed diagnoses of both CM and MOH at screening. Patients were randomly assigned to receive intravenous eptinezumab 100, 300 mg, or placebo every 12 weeks. Efficacy outcomes included mean changes from baseline in monthly migraine days (MMDs) during weeks 1–12, migraine responder rates at week 12, and percentages of patients below International Classification of Headache Disorders thresholds for CM and MOH over weeks 1–24. Results: There were 431 patients who were diagnosed with CM and MOH as specified in the protocol and received eptinezumab 100 mg ( n = 139), 300 mg ( n = 147), or placebo ( n = 145). During the baseline period, these patients experienced an average of 16.7 migraine days across treatment arms. Over weeks 1–12, eptinezumab‐treated patients experienced greater reductions from baseline in MMDs than placebo patients (100 mg, change from baseline = −8.4, difference from placebo [95% confidence interval (CI)] = −3.0 [−4.56, −1.52], p < 0.0001 vs. placebo; 300 mg, change from baseline = −8.6, difference from placebo [95% CI] = −3.2 [−4.66, −1.78], p < 0.0001 vs. placebo; placebo, −5.4). Compared with placebo, more eptinezumab‐treated patients were ≥50% migraine responders (100 mg, 84/139 [60.4%]; 300 mg, 91/147 [61.9%]; placebo, 50/145 [34.5%]) or ≥75% responders (100 mg, 38/139 [27.3%]; 300 mg, 44/147 [29.9%]; placebo, 21/145 [14.5%]) over weeks 1–12. Therapeutic benefits with eptinezumab were observed from day 1 after dosing, and improvements were sustained with an additional dose. For the full 24‐week treatment period, 71/139 (51.1%), 80/147 (54.4%), and 47/145 (32.4%) of 100, 300 mg, and placebo‐treated patients, respectively, were below CM thresholds, and of the patients who provided sufficient acute medication data, 47/93 (50.5%), 53/107 (49.5%), and 26/96 (27.1%), respectively, were below medication‐overuse thresholds. Conclusions: In patients diagnosed with both CM and MOH, eptinezumab treatment resulted in greater reductions in MMDs, higher responder rates, and fewer patients meeting CM and MOH criteria, thus demonstrating the efficacy and clinical utility of eptinezumab in this patient population.